THE CONCEPT OF SOCIAL MEDIA, ITS MEANS, ROLE, TYPES A AND CHARACTERISTICS - Bayinat Basha Al Bajali, Abul Firdaus (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2020)
During this topic, the concept of social media and its definitions, the reasons for their differences, in addition to its means, types and characteristics will be discussed. This study dealt with the issue of social media in the following elements. The concept of social media its means, tools, types, and characteristics. Issues related to social media today are among the topics worthy of study and care, as the media occupies a large and influential space in various fields of life. Perhaps social media is one of the most prominent types of media in terms of influence and importance, as it is based on transmitting news and information from the community to the community itself, to achieve one of the purposes of news, guidance or guidance through its various means such as clubs, forums, places of worship, social networks, newspapers and books. Whereas social media is of such vitality and importance; This topic has been allocated according to the requirements of the study. Whereas social media is of such vitality and importance; This topic has been allocated according to the requirements of the study. This study was based on the extrapolation of the issues in which the opinions of scholars varied according to the multiplicity of factors related to the edge, according to an applied analytical methodology.